Processamento de imagens aplicado a escoamento granular - LOUZADA, Ryan Luis Rodrigues (2023)
This work describes the creation of two algorithms that took place in Matlab to be used in research in the Fluidpar laboratory. The first algorithm is an automatic tool to determine the restriction angle of granular materials, while the second is a computational method to analyze and quantify particle coating in order to evaluate the coating of granular materials. The orientation of the restriction angle is an important parameter in the characterization of granular materials, and the method proposed in this work automates this process, making it more efficient and accurate. The second algorithm is able to evaluate the uniformity of particle coating, which is a critical aspect in many industrial applications of granular materials, allowing a more detailed and quantitative evaluation of this process. Both algorithms showed promising results and have the potential to be applied in future studies in the field of granular materials.